Calculation of the Vehicles Stress-Deformed State while Transporting the Liquid Cargo - Oleksii Grevtsev; Ninel Selivanova; Pavlo Popovych; Liubomyr Poberezhny; Oksana Shevchuk; Igor Murovanyi; Andrii Hrytsanchuk; Liubov Poberezhna; Vasyl Zapukhliak; Galyna Hrytsuliak (Communications - Scientific letters of the University of Zilina, 2021)
To calculate the stress-deformed state of road-tanker metal structures during the liquid cargo transportation, the solution for bending axially and symmetrically loaded circular plates is proposed, which is based on the theory of elasticity approach. Dependencies for calculating stresses and displacements under arbitrary load law and support type are substantiated. Deformation of the support under the action of axisymmetric loading leads to appearance of a temperature field.